Contribution of female directors to cinema and memory regarding ETA terrorism - Labiano , Roncesvalles (2024)
The film industry remains a male-dominated sector, particularly in managerial, creative, and technical positions. In this context, we explore the work of female directors in Spanish cinema concerning ETA terrorism (1977-2023) to observe and assess the contribution of women in a doubly masculine environment: film direction and terrorist violence. Within the framework of the so-called “battle of the narrative” and film and gender studies, and based on a qualitative methodology involving textual analysis of feature films and the study of existing literature, we trace the presence and voice of female directors. We investigate who they are, their number, and their contribution to cinema concerning ETA and Spanish cinema in general. We examine the stories, genres, and themes they choose and the perspectives from which they approach them. We consider both the form and contextual issues related to the production and reception of their works. The results show that female directors are a minority in films about terrorism in Euskadi. We conclude that their work can be seen as a disruption in an adverse environment. They prefer genres such as drama or documentary, focus on a human perspective, several depict real or based-on-true-events stories featuring strong, free female protagonists, and several works approach the stories of victims. They feature characters, predominantly female, who defy stereotypes. Overall, they contribute to the memory of past events with a critical view of violence.